2010
DOI: 10.1186/1472-6823-10-12
|View full text |Cite
|
Sign up to set email alerts
|

Increases in summer serum 25-hydroxyvitamin D (25OHD) concentrations in elderly subjects in São Paulo, Brazil vary with age, gender and ethnicity

Abstract: BackgroundHypovitaminosis D is a common condition among elderly individuals in temperate-climate countries, with a clear seasonal variation on 25 hydroxyvitamin D levels, increasing after summer and decreasing after winter, but there are few data from sunny countries such as Brazil. Many factors can interfere on vitamin D cutaneous synthesis. We aimed at studying the 25OHD variations during winter and summer in an outdoor physically active elderly population living in São Paulo city, and analysed their determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0
11

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 33 publications
4
18
0
11
Order By: Relevance
“…A recent Norwegian study of both lean and morbidly obese persons also found that men had larger seasonal variation of vitamin D concentration than women, in particular young nonobese men (Lagunova et al, 2009). Similar findings have been reported from New Zealand and Brazil, where middle aged and older men had a larger reduction in 25(OH)D during the winter season than women (Bolland et al, 2007;Maeda et al, 2010).…”
Section: Seasonal Variation Vitamin D Intake and Gendersupporting
confidence: 72%
“…A recent Norwegian study of both lean and morbidly obese persons also found that men had larger seasonal variation of vitamin D concentration than women, in particular young nonobese men (Lagunova et al, 2009). Similar findings have been reported from New Zealand and Brazil, where middle aged and older men had a larger reduction in 25(OH)D during the winter season than women (Bolland et al, 2007;Maeda et al, 2010).…”
Section: Seasonal Variation Vitamin D Intake and Gendersupporting
confidence: 72%
“…On the other hand, the variability in iPTH with seasonal climate changes was lower than that for 25-hydroxyvitamin D, as occurred elsewhere (von Mühlen et al, 2005), and the correlation between iPTH and 25-hydroxyvitamin D was less obvious in spring and summer (data not shown), as in other studies (Maeda et al, 2010), probably related with the different turnover of vitamin D3 and iPTH at a time when the production of vitamin D3 in the skin is greater. In general, most studies assume that iPTH reaches a plateau when 25-hydroxyvitamin D values reach a particular concentration (Chapuy et al, 1997;Khosla et al, 1997;Malabanan et al, 1998;Thomas et al, 1998;Leboff et al, 1999;von Mühlen et al, 2005).…”
Section: Discussionmentioning
confidence: 51%
“…Ho wever, three studies involving adolescents showed high prevalence of hypovitaminosis D in this age group of the Brazilian population (6466). The factors that seem to favor the presence of higher serum concentrations in our population are: younger age (64,6769), commu nity life (70), the practice of outdoors physical activity (64,71), vitamin D oral supplementation (72), season of the year (spring, summer) (6873), residence in sun ny beach areas (74,75) and in lower latitudes (76). Current evidence does not support the concept of general population supplementation (41) (A).…”
Section: What Are the Effects On Bone Metabolism?mentioning
confidence: 99%